EFFECTS OF GLOBAL WARMING ON FISHERIES (Third Sector Social Economic Review, 2018)
The global warming process and all the aquatic environments in the earth react to this warming, and as a result, it is thought that with varying physicochemical properties, there will be many consequences affecting the living conditions of aquatic ecosystems. In the fisheries and aquaculture sectors, which are currently under pressure by non-climate factors, this pressure can be transformed into an unmanageable scenario with factors arising from climate change. In addition to non-climate factors that create stress on stocks such as over-fishing, pollution, habitat destruction; as a result of global warming; all the aquatic organisms are affected by such changes as temperature increase in sea and fresh water, acidification, sea level rise, precipitation and water quality changes. These factors may change the fish stocks as species composition, recruitment, product and yield, species tolerance levels, distribution and migration. Increasing in disease types in any habitat and damage increase in coral reefs also supply chain and product costs may deteriorate. In addition, climate change will have an impact on economic fisheries as competition, migration and sector change, as well as increase in fish demand and consumption in humans as consumers.
Keywords: Global warming; climate change; fish stocks; fisheries; aquaculture